Biologic characterization of ABCA3 variants in lung tissue from infants and children with ABCA3 deficiency. Issue 5 (17th March 2022) - Xu, Kathryn K.; Wegner, Daniel J.; Geurts, Lucille C.; Heins, Hillary B.; Yang, Ping; Hamvas, Aaron; Eghtesady, Pirooz; Sweet, Stuart C.; Sessions Cole, F.; Wambach, Jennifer A.
Abstract: ABCA3 is a phospholipid transporter protein required for surfactant assembly in lamellar bodies of alveolar type II cells. Biallelic pathogenic ABCA3 variants cause severe neonatal respiratory distress syndrome or childhood interstitial lung disease. However, ABCA3 genotype alone does not explain the diversity in disease presentation, severity, and progression. Additionally, monoallelic ABCA3 variants have been reported in infants and children with ABCA3‐deficient phenotypes. The effects of most ABCA3 variants identified in patients have not been characterized at the RNA level. ABCA3 allele‐specific expression occurs in some cell types due to epigenetic regulation. We obtained lung tissue at transplant or autopsy from 16 infants and children with ABCA3 deficiency due to compound heterozygous ABCA3 variants for biologic characterization of the predicted effects of ABCA3 variants at the RNA level and determination of ABCA3 allele expression. We extracted DNA and RNA from frozen lung tissue and reverse‐transcribed cDNA from mRNA. We performed Sanger sequencing to assess allele‐specific expression by comparing the heights of variant nucleotide peaks in amplicons from genomic DNA and cDNA. We found similar genomic and cDNA variant nucleotide peak heights and no evidence of allele‐specific expression among explant or autopsy samples with biallelic missense ABCA3 variants ( n  = 6). We observed allele‐specific expression of missense alleles in trans with frameshift ( n  = 4) or nonsense ( n  = 1) variants, attributable to nonsense‐mediated decay. The missense variant c.53 A > G;p.Gln18Arg, located near an exon‐intron junction, encoded abnormal splicing with skipping of exon 4. Biologic characterization of ABCA3 variants can inform discovery of variant‐specific disease mechanisms.